2015
DOI: 10.18203/issn.2454-2156.intjscirep20150216
|View full text |Cite
|
Sign up to set email alerts
|

A study of prevalence of primary hypothyroidism in recently diagnosed type 2 diabetes mellitus in a tertiary care hospital

Abstract: <p class="abstract"><strong><span lang="EN-US">Background: </span></strong>The association between thyroid dysfunction and DM has long been recognized, although the prevalence of thyroid dysfunction among diabetes population varies in different studies. This study destined to know the prevalence of thyroid dysfunction of recently diagnosed type 2 diabetes mellitus patients.  </p><p class="abstract"><strong><span lang="EN-US">Methods: </span></stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In its clinical form, hypothyroidism is a relatively common condition, with an approximate prevalence of 2% in adult women and 0.2% in adult men [3]. The clinical features of hypothyroidism are dependent on the patient's age, the presence of other diseases, and the rate at which hypothyroidism develops [4].…”
Section: Introductionmentioning
confidence: 99%
“…In its clinical form, hypothyroidism is a relatively common condition, with an approximate prevalence of 2% in adult women and 0.2% in adult men [3]. The clinical features of hypothyroidism are dependent on the patient's age, the presence of other diseases, and the rate at which hypothyroidism develops [4].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of thyroid dysfunctions in type 2 diabetes mellitus varies in literature from very low (5.5%) to very high (75%). 8,13 Till date, there is no consensus regarding actual prevalence. So, the aim of this study was to find out the prevalence of thyroid dysfunction in type 2 diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported varying prevalences (10%-24%) of thyroid dysfunction in type 2 diabetes [10]. The prevalence of thyroid dysfunction in type 2 diabetes varies in the literature from very low (5.5%) to very high (75%) [11,12]. Thyroid disease is more widespread among the diabetic population as compared to the population of normal individuals [13][14][15].…”
Section: Introductionmentioning
confidence: 99%